Distribution of the Peruvian Plantcutter Phytotoma raimondii (Passeriformes: Cotingidae) - Flanagan, Jeremy N. M. (2009)
The Peruvian Plantcutter, Phytotoma raimondii Taczanowski, 1883, is a restricted-range species endemic to coastal northern Peru. Historically its range is given from Tumbes in the extreme north-western Peru, south to the northern part of Lima Department. Although an increasing amount of information on the Peruvian Plantcutter exists, from historical records to new locations, it has remained dispersed, sometimes unverified, not systematized, and largely unpublished. A careful revision of museum collections as well as published and unpublished records results in a total of 53 sites where the species has been recorded and that represent the present knowledge of the distribution of the species.